2013
DOI: 10.5209/rev_cuts.2013.v26.n2.40915
|View full text |Cite
|
Sign up to set email alerts
|

Una aproximación al Trabajo Social desde la óptica de la Psicología positiva (virtudes y fortalezas)

Abstract: ResumenLa Psicología positiva es una ciencia social de desarrollo relativamente reciente que analiza las bases del bienestar psicológico a partir de las fortalezas y virtudes de cada individuo y de sus potencialidades de influir en los otros para el logro de la plenitud y desarrollo personal.En el marco de la Psicología positiva se aplicó el test VIA-IS a 186 estudiantes de primer curso de Grado en Trabajo Social en la Universidad Complutense de Madrid durante el curso 2011-2012. El objetivo de la presente inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Although, higher levels of engagement were associated with males and lower levels were associated with females, as the present study showed, where men get higher engagement scores than women. In engagement studies, men and women have shown improved mental health [ 83 ], influencing their personal psychological and spiritual well-being [ 84 ], as a person who is perceived competent in practice could have a more positive attitude, thereby finding himself or herself more motivated.…”
Section: Discussionmentioning
confidence: 99%
“…Although, higher levels of engagement were associated with males and lower levels were associated with females, as the present study showed, where men get higher engagement scores than women. In engagement studies, men and women have shown improved mental health [ 83 ], influencing their personal psychological and spiritual well-being [ 84 ], as a person who is perceived competent in practice could have a more positive attitude, thereby finding himself or herself more motivated.…”
Section: Discussionmentioning
confidence: 99%
“…Por su parte, también dentro del Trabajo Social, Reamer (2006Reamer ( , 2017, inspirándose en Beauchamp y Childress, señala como cualidades importantes de las y los trabajadores sociales la compasión, la confianza, la integridad, el discernimiento y la diligencia (conscientiousness). Destacaremos también el estudio realizado entre el alumnado de primero de Grado de Trabajo Social en la Universidad Complutense de Madrid utilizando el Inventario de Fortalezas Virtue in Action (Jiménez et al, 2013).…”
Section: Aproximando La éTica De La Razón Cordial Al Trabajo Socialunclassified
“…The different development of character strengths that comprise this quality (two of the highest scoring and two of the lowest) causes a degree of inconsistency in the case of advanced musicians or students, as they do not usually resemble what is conventionally considered "wise" or "learned" people. Nonetheless, the least developed virtues coincide with these studies -temperance and transcendence-probably due to the age of the participants and their sociocultural context (Calderón-Garrido, Forés-Miravalles & Gustems-Carnicer, 2016;Gustems & Calderón, 2015;Jiménez, Alvarado & Puente, 2013;Saldaña et al, 2014).…”
Section: Discussionmentioning
confidence: 62%